Pengaruh Media Sosial dan Web Quality terhadap Citra Merek pada Malang Autism Center di Kota Malang (Studi Kasus pada Akun Instagram dan Komunitas Malang Autism Center) - Purnama, Muhammad Bintang Widya; Primanto, Alfian Budi; Arsyianto, Muhammad Tody (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to identify and analyze the influence of social media and web quality on brand image at Malang Autism Center in Malang City (Case Study on Instagram Account and Malang Autism Center Community). The population in this study The general population in this study are followers of the MAC account, consumers, communities gathered by the Malang Autism Center, visitors on the website, Community Members of the Malang Autism Center or Recipients of educational / therapy services from the Malang Autism Center and also Malang Autism Center Instagram followers with ages 17 - 60 years While the sample in this study amounted to 85 samples. Data analysis using Multiple Linear Regression. The results of this study indicate 1) Social media has a positive but insignificant effect on brand image 2) Web quality has a positive and significant effect on brand image 3) Social media and web quality have a simultaneous effect.  Keywords: Social Media, Web Quality, Brand Image, Autism